Graph Theory as A Tool for Growing Mathematical Creativity - Puput Suriyah; Stevanus Budi Waluya; Rochmad Rochmad; Wardono Wardono (Jurnal Pendidikan Edutama, 2020)
Abstrac: The purpose of this research to describe about graph theory is subject can serve as a tool for growing mathematical creativity. Systematic Literature Review (SLR) is used as a method of analyzing a wide range of articles and literature were obtained through searching of data sources. The results of the analysis of various sources elaborated reviews about the open ended questions of graph theory that are used as a disclosure in growing the mathematical creativity of students based on Bahar & Maker's theory modifications are open ended questions that have characteristics such as fluency and flexibility and have been done in detail/elaboration. Fluency on theory graph can be known when students do task/exercises such as isomorphic graph. Flexibility on theory graph can be known when students do task/exercises, example about spanning trees. In this paper also we showed how can use graph theory to teach standards of NCTM (National Council of Teachers on Mathematics of America) that related with mathematical creativity. Keyword: graph theory, mathematical creativity, fluency, flexibility  Abstrak: Tujuan penelitian ini untuk mendeskripsikan graf teori merupakan salah satu alat untuk menumbuhkan kreativitas matematika. Systematic Literature Review (SLR) digunakan sebagai metode dalam menganalisis sebagai berbagai artikel dan literatur yang diperoleh melalui pencarian sumber data. Hasil analisis dari berbagai sumber tersebut dijabarkan ke dalam ulasan tentang pertanyaaan terbuka dari teori graf yang digunakan untuk mengungkap tumbuhnya kreativitas matematika peserta didik berdasarkan teori modifikasi Bahar & Maker dimana pertanyaan terbuka yang memiliki karakteristk seperti fluency/kelancaran dan flexibility/keluwesan yang dikerjakan secara elaborasi. Dimensi fluency/kelancaran pada teori graf dapat diketahui ketika peserta didik mengerjakan soal misal tentang isomorfik. Dimensi flexibility/keluwesan pada teori graf dapat diketahui ketika peserta didik mengerjakan soal misal tentang spanning trees/pohon berentang. Dalam artikel ini ditunjukkan juga bagaimana graf teori menggunakan standar dari NCTM yang terkait dengan kreaitvitas matematika. Kata kunci: teori graf, kreativitas matematika, fluency, flexibility